Sex Education or Education “For“ Sex - Croatian Sex Education Curriculum Observed Through the Intercultural Prism - Bartulović, Marija pedagoginja (2009)
This paper has two starting points: first, intercultural education includes dealing with different types of diversity, not only cultural, racial, national, ethnic ; but also sexual, gender, religious and other, involving the acceptance of other as different ; and second, sex education has not yet, in spite an obvious need, become a part of curriculum in Croatian educational system. Considering those two points, we will try to outline the main problems appearing in our society that is still rather conservative when it comes to those important social topics. Sex education has been a field of many controversial debates in Croatia, after an educational policy-level decision was made about its implementation in official public school program. Two opposite sides were confronted, one proclaiming abstinence-only program based on catholic values, while the other based its program on scientific research on human sexuality and liberal values. Due to inability of accomplishing consensus on a national level, both programs were accepted as appropriate, leaving parents to decide what should their children be taught in schools, when it comes to sex. After a year of experimental implementation, policy-makers have decided there is no need for sex education in Croatia. In order to help prevent further superficial, sensationalistic approaches creating space for different kinds of manipulations in educational field, we will try to give a critical overview of the programs, as well as a possible alternative or update from intercultural perspective. As a framework, we will use evaluation of a Sexual Pedagogy Course implemented recently at our Department of Pedagogy, presented through results of a research among students taking the course, and those who are not as a control group ; on knowledge and attitudes about sexual diversity, and gender roles and sexual stereotypes as a basis of discrimination. The main aim is to outline that sex education needs to include a holistic view on human sexuality and deal the problems of values, sexual stereotyping, gender roles, prejudice and discrimination, which are some of the main problems of our society. Our intention is to give a constructive contribution in shaping sex education curriculum, based on an intercultural educational paradigm, promoting acceptance and respect of all types of diversities, since many of prejudices and boundaries are social constructions we are often not aware of, implemented in our way of thinking and approaching the world around us.